1990
DOI: 10.1063/1.345261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver doping in the high-T c superconductor system Y-Ba-Cu-O

Abstract: Changes in various superconducting properties as a function of silver substitution in the bulk granular high-Tc system Y-Ba-Cu-O have been investigated. In the low doping limit, Ag impurities behave as an excellent oxygen stabilizer and the critical current density is enhanced by an order of magnitude while the Tc remains practically unchanged. When the Ag content is increased to above 20%, the Tc starts to drop and the effects of Ag clusters as well as impurity phases become more important. However, the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[5][6][7] In general, small amounts of added noble metal substitute for Cu in the crystal structure. 5,7 Thin film Ag composites have also been prepared from composite targets. 5,7 Thin film Ag composites have also been prepared from composite targets.…”
Section: Thin Film Composites Of Au and Yba 2 Cu 3 O 7؊␦mentioning
confidence: 99%
“…[5][6][7] In general, small amounts of added noble metal substitute for Cu in the crystal structure. 5,7 Thin film Ag composites have also been prepared from composite targets. 5,7 Thin film Ag composites have also been prepared from composite targets.…”
Section: Thin Film Composites Of Au and Yba 2 Cu 3 O 7؊␦mentioning
confidence: 99%
“…These materials have exhibited lower than the usual reports for epitaxial YBCO on single-crystal substrates. However, reproducibility problems with oxygen stoichiometry and impurities along the grain boundaries were found for the granular films, and for the polycrystalline films there has been no obvious, effective technique for systematically controlling at temperatures well below the transition temperature Studies of composite materials in both bulk and thin film forms have shown more promise in addressing these issues [6], [7]. The presence of small amounts of Ag has been shown to stabilize oxygen stoichiometry and improve the microstructure.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4] Several groups have studied the effect of the addition of noble metals to the YBCO matrix [5][6][7][8][9][10][11][12][13][14][15] and among the noble metals silver (Ag) is observed to be the least reactive and causes no serious degradation of superconducting properties of YBCO. 17 The silver is also observed to segregate as fine grains at the grain boundaries and helps in improving the contact properties between the neighboring grains. For example, silver is reported to form an unstable silver oxide, which decomposes later at high temperatures, releasing oxygen and making it extremely useful in sintering of YBCO.…”
Section: Introductionmentioning
confidence: 99%
“…At low silver concentrations the silver is reported to act as an excellent oxygen stabilizer and improves the transport properties. 17,26 At high enough Ag concentration, Ag can abstract large amount of oxygen from YBCO grains forming nonsuperconducting YBa 2 CuO 5 -211 and CuO. 18 The silver on 123 surfaces exhibits very high contact conductivity 19 and can be utilized as an oxygen diffusion barrier, 20,21 as well as passivation buffer against water degradation.…”
Section: Introductionmentioning
confidence: 99%